Peran Undang-Undang Perlindungan Anak dalam Mengatasi Bullying di Sekolah - Dinda Kania Anggraini; Muchammad Rozaq F H; Tristan Salahudin S; Sayekti Putri D (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2024)
This study aims to analyze the forms, causes of bullying and legal protection for child victims of bullying referring to Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. The author uses a normative juridical research approach, which utilizes legal sources as the primary source in this research. In addition, this research is also supported by additional legal sources through literature studies. The results of this study show that bullying has several forms, including bullying with direct verbal contact, direct physical contact, direct non-verbal behavior, indirect non-verbal behavior, cyber bullying, and sexual harassment. Factors that cause the perpetrator to commit acts of bullying include the family environment and psychological disorders in the perpetrator. And legal protection for child victims of bullying has been regulated in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection, where the perpetrators of bullying can be sentenced to fines to imprisonment.